Role of basic leucine zipper proteins in transcriptional regulation of the steroidogenic acute regulatory protein gene - Manna, Pulak R. (Mol Cell Endocrinol, 2008)
The regulation of steroidogenic acute regulatory protein (StAR) gene transcription by cAMP-dependent mechanisms occurs in the absence of a consensus cAMP response element (CRE, TGACGTGA). This regulation is coordinated by multiple transcription factors that bind to sequence-specific elements located approximately 150 bp upstream of the transcription start site. Among the proteins that bind within this region, the basic leucine zipper (bZIP) family of transcription factors, i.e. CRE binding protein (CREB)/CRE modulator (CREM)/activating transcription factor (ATF), activator protein 1 (AP-1; Fos/Jun), and CCAAT enhancer binding protein β (C/EBPβ), interact with an overlapping region (−81/−72 bp) in the StAR promoter, mediate stimulus-transcription coupling of cAMP signaling and play integral roles in regulating StAR gene expression. These bZIP proteins are structurally similar and bind to DNA sequences as dimers; however, they exhibit discrete transcriptional activities, interact with several transcription factors and other properties that contribute in their regulatory functions. The 5′-flanking −81/−72 bp region of the StAR gene appears to function as a key element within a complex cAMP response unit by binding to different bZIP members, and the StAR promoter displays variable states of cAMP responsivity contingent upon the occupancy of these cis-elements with these transcription factors. The expression and activities of CREB/CREM/ATF, Fos/Jun and C/EBPβ have been demonstrated to be mediated by a plethora of extracellular signals, and the phosphorylation of these proteins at several Ser and Thr residues allows recruitment of the transcriptional coactivator CREB binding protein (CBP) or its functional homolog p300 to the StAR promoter. This review will focus on the current level of understanding of the roles of selective bZIP family proteins within the complex series of processes involved in regulating StAR gene transcription.